Cognitive Impairment and Magnetic Resonance Imaging Correlates in Primary Progressive Multiple Sclerosis - Gouveia, A (2022)
Objectives: To characterize cognitive impairment in primary progressive multiple sclerosis (PPMS) and to correlate the pattern of cognitive deficits with brain magnetic resonance imaging (MRI) volumetric data. Materials and methods: In a multicenter cross-sectional study, we recruited consecutive patients with PPMS as well as age, sex, and education level-matched healthy controls (HC). All participants underwent neuropsychological (NP) assessment, and brain MRI was performed in patients with PPMS for analysis of lesion load, subcortical GM volumes, and regional cortical volumes. Results: We recruited 55 patients with PPMS and 36 HC. Thirty-six patients were included in the MRI analysis. Patients with PPMS performed significantly worse than HC in all NP tests. Subcortical GM volume was significantly correlated with all NP tests, except for Stroop Test, with the largest effect for the thalamus (r=-.516 [BVMT-R DR, P=.016 FDR-corrected] to r=.664 [SDMT, P<.001 FDR-corrected]). In the stepwise linear regression model, thalamic volume was the only predictor of performance in all NP tests. Conclusion: Cognitive impairment is common in PPMS and affects all evaluated cognitive domains. Subcortical GM volume, particularly of the thalamus, is a strong predictor of cognitive performance, suggesting it has a central role in the pathophysiology of PPMS-related cognitive dysfunction.